Pendidikan Anak Supernormal dengan Pendekatan Living Values Education Program (Studi Kasus Kelas Akselerasi MAN 2 Kota Madiun) - Asfahani Asfahani; Wiwin Rif’atul Fauziyati (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
The purpose of this study was to determine the strategies, approaches, stages and results of the life value education program in the education of supernormal children in MAN 2 Madiun City. Qualitative research method was conducted by direct observation and gained the results of this study which were that the Living Values Education Program (LVEP) acceleration class of MAN 2 in Madiun City is done by habituation, lecture, hands-on practice, discussion, performance, assignments, and visits to religious places, and uswah hasanah. The holistic approach (integrated and synchronized) in which the development of character values is integrated and interconnected in all aspects of the madrasa environment. The stages of reviving the value in children accelerated starting with the quarantine process. Through this LVEP, it is certain that children have personalities based on religious and cultural noble values. The conclusion of this research is that the LVEP approach has delivered supernormal children of MAN 2 Madiun City to have an awareness of high values, virtuous character and aware of the importance of exemplary and practice of values themselves in appreciating